The effect of water consumption level on dehydration status and archery accuracy in Banyumas Regency archery athletes - Cahyo, F. D.; Prasetyo, Y.; Rismayanthi, C.; Delano, E. H. (Journal of Sports Science and Nutrition, 2023)
This study aimed to determine the effect of water consumption levels on dehydration status and archery accuracy on archery athletes in the Banyumas Regency. This research was based on the observations and experiences of the researchers, who found that there was still a lack of awareness among archery athletes in Banyumas Regency to meet their hydration requirements properly. In addition, there were still many archery athletes in Banyumas Regency who did not carry enough drinking water during practice.